엔테로코커스 페컬리스 유래의 독성인자의 동정과 응용: 특성, 고정화, 하이드로젤 형성 - 장은진 (The Graduate School, Ajou University, 2014)
The virulence factors from pathogenic bacteria are useful for industrial applications because of their high stabilities and catalytic properties under harsh conditions. Here, characterization, immobilization, and hydrogel formation of a virulence factor, namely, EfEstA from Enterococcus faecalis are presented. The molecular characteristics of EfEstA were investigated by performing SDS-PAGE, zymogram assay, dynamic light scattering, mass spectrometry, enzyme assays, molecular modeling, circular dichroism spectroscopy, and fluorescence analysis. In addition, cross-linked enzyme aggregates (CLEAs) of EfEstA exhibited high recycling processes and improved stabilities compared to free EfEstA. Furthermore, macroscopic hydrogels of EfEstA could be used as an environment friendly carrier to absorb several metal ions. These characteristics of EfEstA shed light on the design and fabrication of new biomaterials based on bacterial virulence factors for the pharmaceutical, biotechnological, and chemical industries.
학위논문(석사)--아주대학교 일반대학원 :분자과학기술학과,2014. 2
Keywords: virulence factor; CLEAs; Hydrogel